Validity and reliability of the Colorado Adult Joint Assessment Scale in adults with moderate‐severe hemophilia A. (13th November 2019) - Funk, Sharon M.; Engelen, Sylvia; Benjamin, Katy; Moshkovich, Olga; Gentile, Brittany; Church, Nikki; Hong, Walter; Thornhill, Dianne; Manco‐Johnson, Marilyn J.
Abstract: Background: The Colorado Adult Joint Assessment Scale (CAJAS) is designed to assess joint health in adults with hemophilia. The CAJAS comprises nine items (swelling, muscle atrophy, axial deformity, crepitus, range of motion, contracture, instability, strength, gait) and assesses six joints. Objective: To assess CAJAS content validity and psychometric properties. Patients/Methods: Data were obtained from the Trial to Evaluate the Effect of Secondary Prophylaxis With rFVIII Therapy in Severe Hemophilia A Adult and/or Adolescent Subjects Compared to That of Episodic Treatment (SPINART) study and a separate CAJAS validation study. CAJAS assessments in SPINART were performed by physical therapists (PTs) from the United States, Romania, Bulgaria, and Argentina. In the validation study, content validity was assessed from interviews with six PTs at three US hemophilia centers; cultural equivalence was assessed with seven non‐US PTs from SPINART. Reliability data were collected from 30 subjects at four US centers. Test‐retest reliability was evaluated by having the same PT perform CAJAS examinations at two visits, 7‐10 days apart. Inter‐rater reliability was assessed by comparing CAJAS scores of two different PTs performing separate examinations of the same patient several hours apart at the same visit. Psychometric properties were assessed using SPINART and validation study data. Results: The CAJAS demonstrated good content validity. Test‐retest reliability was high (intraclass correlation coefficient, 0.98), as was inter‐rater reliability (intraclass correlation coefficient, 0.88). Internal consistency reliability was strong ( α  = .90). The CAJAS demonstrated good convergent/divergent validity, known‐groups validity, and ability to detect change. Conclusions: The CAJAS is a valid and reliable measure of joint health in adults with moderate‐severe hemophilia and is appropriate for use in clinical practice.